MENDELEY TRAINING FOR WRITING CITATIONS OF SCIENTIFIC WORKS FOR STUDENTS - Clan, Edward (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of conducting training is so that students can produce scientific works and test the extent of mastery of knowledge obtained during the lecture period in the form of scientific writing. The methods used are socialization and training. The results obtained from the training activities on the use of the Mendeley Reference Manager application show an increase in students' knowledge and abilities in using the Mendeley Reference Manager application after participating in the training activities. The criteria for achieving training activities are very good with a value of 4.52. The suggestion from this activity is to carry out training with a similar reference manager application.